2016
DOI: 10.1074/jbc.m116.730481
|View full text |Cite
|
Sign up to set email alerts
|

The Human 343delT HSPB5 Chaperone Associated with Early-onset Skeletal Myopathy Causes Defects in Protein Solubility

Abstract: Mutations of HSPB5 (also known as CRYAB or ␣B-crystallin), a bona fide heat shock protein and molecular chaperone encoded by the HSPB5 (crystallin, alpha B) gene, are linked to multisystem disorders featuring variable combinations of cataracts, cardiomyopathy, and skeletal myopathy. This study aimed to investigate the pathological mechanisms involved in an earlyonset myofibrillar myopathy manifesting in a child harboring a homozygous recessive mutation in HSPB5, 343delT. To study HSPB5 343delT protein dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Propensity to aggregation in vitro and in vivo is a nearly universal feature of the analyzed CRYAB mutations (Table 5), which has been demonstrated for p.R120G [222,262,263,271,272] as well as several other mutations [227,258,259,[272][273][274]. CRYAB p.R120G expressed in cells or transgenic tissues forms aggregates that coalesce into perinuclear aggresomes [262,271].…”
Section: Aggregation and Amyloid Formationmentioning
confidence: 78%
See 4 more Smart Citations
“…Propensity to aggregation in vitro and in vivo is a nearly universal feature of the analyzed CRYAB mutations (Table 5), which has been demonstrated for p.R120G [222,262,263,271,272] as well as several other mutations [227,258,259,[272][273][274]. CRYAB p.R120G expressed in cells or transgenic tissues forms aggregates that coalesce into perinuclear aggresomes [262,271].…”
Section: Aggregation and Amyloid Formationmentioning
confidence: 78%
“…Functional studies on p.S115Pfs*14 revealed that the mutant protein is extremely insoluble, but its solubility is increased upon the coexpression of wild-type CRYAB [274]. Overexpression of the mutant protein in BHK21 cells produced aggregates, some of which contained desmin, and it also elicited a stress response [274].…”
Section: Recessive αB-crystallinopathymentioning
confidence: 99%
See 3 more Smart Citations